Physical, physicochemical and phytochemical characterization of the latex of the Janaúba plant (Euphorbia Umbellata) of the varieties Synadenium granti hook and Synadenium umbellatur pax - Pires, Márlia Barbosa; Conceição, Adriana Lima da Silva da; Silva, Mickelly Farias e; Quemel, Gleicy Kelly China; Pinto, Yasmin Bentes (Seven Editora, 2023)
The use of medicine plants for the healing is used since the begginings, but the rise of the reseraches and the advance of the science, most of the these plants already have the evidenced effectiveness by scientific evidences checked. Therefore, a study about the plant Euphorbia umbellata and its varieties would have great relevance, since it is popularly very known when it comes to its physiotherapeutic action in the ancologic treatment. The species belonging to this group posses great highlight not inly in the economic acticity directly related to the human alimentation but also in the popular medicine based on the empiric knowledge. To characterize physical-chemical and phatochemical the latex of the Janauba plant (Euphorbia umbellata) of the varieties Synadenium grant Hook and Synademium umbellatur Pax. The sampling stock used in the research was collected in Belém and municipalities and Castanhal city, in Pará state, Brazil, between April and November pf 2022. It was taken to the controll and quality laboratory of Centro Universitário da Amazônia (UniEsamaz) located in Belém, PA, for the execution of the analyzes. The anatomic characterization is fairly important because it must be done before the use related to the medicine plant, in what way it can be idetified in other not to occur a wrong consume of the specie. The sample results demonstrate that the latex of Janauba is a product classified as medium acidity, the difference of PH, based on the results obtained do not demonstrate great impact. Thus, it is concluded that despite they have not detected in the current analyses and comparing to the previous results, the Janauba plant and its varieties can be considered as a strong alternative to help the cancer comba and being extremaly essential when it is used due to the presence of cumarinas which can cause hepatic problems for the use of big quantities. DOI:https://doi.org/10.56238/interdiinovationscrese-012